ANALISIS BUKU AJAR BAHASA ARAB MADRASAH TSANAWIYAH: TINJAUAN MUFRADAT DALAM PERSPEKTIF RUSYDI AHMAD THU'AIMAH - Akhiryani, Atna; Nur Rahma Cahyani, Annisa; Ahmad Asse (Program Studi Pendidikan Bahasa Arab (PBA), Universitas Islam Negeri Datokarama Palu, 2024)
Vocabulary in Arabic is known as مفردات, the plural form of the word مفردة. The word mufradāt is equivalent to the word “vocabulary”, with the meaning of a word that has its meaning in a language. Mufradāt is an essential aspect of learning Arabic. In this regard, the explanation in this thesis begins with the quality and quantity of mufradāt and the suitability of the basic principles of mufradāt in the Arabic language textbook using Rusydi Ahmad Thu’aimah’s theory. The research uses a qualitative approach with the type of library research, data collection techniques using documentation techniques, while the data analysis technique used is content analysis techniques. The research results found 216 mufradāt, with 92 mufradāt musytaq and 125 mufradāt jamid. The suitability of mufradāt with the theory used in this textbook does not meet the basic principles of selecting mufradāt, according to Rusydi Ahmad Thu’aimah’s theory.